Femoral Neuropathy: A Rare Presentation of Retroperitoneal Hematoma with Review of Literature - Sahu, Kamal Kant (Indian J Hematol Blood Transfus, 2019)
Hematomas in close compartments and in pelvic gutters are always challenging to treat and diagnose. A young female on apixaban for recently diagnosed pulmonary thromboembolism (PE) presented to us for the complaints of right sided lower limb weakness. Neurological examination was positive for the right femoral nerve distribution deficit. Computed tomography (CECT) showed large right sided iliopsoas hematoma. Anticoagulation was stopped and was given blood transfusions with which she improved without need of any surgical evacuation. We hereby aim to enrich the understanding of our readers regarding this topic with a review of our experience and other recent publications in medical literature. It is important for the internists to be aware of varied and atypical presentations of retroperitoneal hematoma (RPH) especially following surgical/orthopaedic procedures or in association with anticoagulants and antiplatelets.